Implementation of Learning Strategies based on Reflective Learning Theory to Improve Students’ Self-Efficacy in Learning English - Ratri Nur Hidayati (Ahmad Dahlan Journal of English Studies, 2015)
Self-Efficacy means the belief in one's capabilities to achieve a goal or an outcome. Efficacy beliefs play an influential meditational role in academic attainment. While Reflective learning can be described as tending to think deeply about the knowledge obtained by study. Reflection is the indication of deep learning because it helps students learn through reflection, precisely because of the established link between reflection and deeper learning. Reflective learning is closely related to improve Self-efficacy. Thus this article aims at elaborating the effective English learning strategies based on reflective learning theory to improve students’ self- efficacy. This paper proposes some actions, i.e. implementing oral reflective learning on action, oral reflective learning in action and written reflective learning. In improving the students’ self-efficacy in learning in the forms of (1) the improvement of students’ appreciation of social resources, (2) the improvement of students’ courage in achieving academic performances, (3) the improvement of students’ consistency for self- regulated learning, and (4) the improvement of students’ social self-efficacy.